PENGARUH STRUKTUR KEPEMILIKAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL REPONSIBILITY PADA PERUSAHAAN HIGH PROFILE DI BEI - Zulkifli Zulkifli; Diah Khairiyah; Nensi Yuniarti ZS (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2022)
This research was conducted to see the effect, of foreign share ownership, managerial share ownership, and institutional share ownership, on Corporate Social Responsibility (CSR) disclosure. This research is a quantitative descriptive research method using secondary data. Determination of the sample using the purposive sampling method in order to obtain a sample of 35 samples from 110 companies. Analysis of the data used is a multiple linear regression analysis using the IBM SPSS Statistic 16 application. The results of this study indicate that foreign share ownership has no effect on Corporate Social Responsibility (CSR) disclosures with a significant value of 0.650, managerial stock ownership has an effect on Corporate Social Responsibility (CSR) disclosures with a significant value of 0.047, institutional share ownership has an effect on corporate social disclosures. Responsibility (CSR) with a significant value of 0.010. Simultaneously foreign share ownership, managerial share ownership, and institutional share ownership have a significant effect on the disclosure of Corporate Social Responsibility (CSR) with a significant value of 0.002.